A COMPARATIVE STUDY OF THE STUDENTS’ ACHIEVEMENT ON READING BETWEEN USING MULTIPLE CHOICE TEST AND ESSAY TEST; A CASE STUDY AT THE SECOND YEAR STUDENTS OF SMPN 1 JANAPRIA IN ACADEMIC YEAR 2022/2023 - Karimah Karimah; Laili Mardatillah (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2024)
This research entitle Comparative Study of the Students’ Achievement on Reading Between Using Multiple Choice Test and Essay Test; A Case Study at Second Year Students of SMPN Negeri 1 Janapria in Academic Year 2022/2023. It was aimed to know difference on students’ achievement on reading between using multiple choice and essay test at the second year students of SMP Negeri 1 Janapria in Academic Year 2022/2023 and factors that promote the effectiveness of students’ achievement on reading between using multiple choice and essay test. The sample in this investigation consists of 28 students. The data are collected using test, namely essay test and multiple choice test. The researcher administered the essay test which consists of 20 items and multiple choice test which consists of 20 items. The result of using multiple choice test and essay test are analyzed by r = 0.484 and mean score of both are multiple choice(X)= 71.79, essay test (Y) = 65.57 and the value of t = 2.82. Based on the explanation above, it is concluded that there was difference on students’ achievement of the students who were taught by using multiple choice test than those who were taught by using essay test.